Surgical excision of an inverted-Y frenum - Moitri Ojha; Deepika Pawar Chandrashekara Rao; Pratibha Shashikumar; J T Madhushree (Wolters Kluwer Medknow Publications, 2023)
Frenula of the oral cavity consist of the labial, buccal, or lingual frenum. They are folds of mucous membrane enclosing connective tissue. Clinically, an abnormal/aberrant frenum can pull the gingival margins causing recession, plaque accumulation, pocket formation, or midline diastema. Furthermore, in edentulous ridges, high frenal attachment can interfere with the denture margins affecting its stability. Frenotomy and frenectomy are common surgical approaches for such conditions. This case report highlights the frenectomy of inverted-Y frenula with a wide base as a means of preprosthetic surgery.